2008
DOI: 10.1200/jco.2008.16.2768
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-Related Osteonecrosis of the Jaws: A Case-Control Study of Risk Factors in Breast Cancer Patients

Abstract: The outcome of the present study suggests early referral by oncologists for dental evaluation for every patient to be treated with BP. These results raise the current American Society of Clinical Oncology Level of Evidence linking certain dental procedures with ONJ from V to III. Further studies are needed to assess other possible risk factors and also to highlight the etiopathogenesis mechanism of ONJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(135 citation statements)
references
References 13 publications
6
126
0
3
Order By: Relevance
“…Several risk factors for ONJ have been identified [7,8,11,15,16,[30][31][32][33]. One of the most commonly associated risk factors in cancer patients is the use of intravenous bisphosphonate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for ONJ have been identified [7,8,11,15,16,[30][31][32][33]. One of the most commonly associated risk factors in cancer patients is the use of intravenous bisphosphonate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…gingiva or palatal tissue, is composed of stratified epithelium and thin connective tissue; furthermore, it is considered to be one of the most protective tissue barriers against physical and chemical damage, bacterial infection, and environmental stress (14). Case control studies of patients with ONJ have indicated an increased risk of developing this condition with tooth extraction or the use of ill-fitting removable dental prostheses (15,16). These "event-related" oral conditions among BPtreated patients can lead to inflammation in the oral mucosa tissue that likely activates oral barrier immunity.…”
Section: Osteonecrosis Of the Jaw (Onj)mentioning
confidence: 99%
“…[19][20][21][22][23][24] BRONJ usually occurs more frequently in patients receiving nitrogen-containing bisphosphonates via parenteral route than oral administration. [24][25][26][27] Researchers reported the incidence of BRONJ after oral surgery (like tooth extraction) with cancer patients receiving intravenous bisphosphonates between 6.5% and 51.8%. [28][29][30] Historically, the risk of developing osteonecrosis (at any site) is four times higher in cancer patients than in the normal population and has multiple risk factors, including previous/ concomitant chemotherapy, regular steroid therapy, immunosuppressant therapy, radiation therapy, diabetes, hypertension, obesity, certain gene mutations, tobacco habit, alcoholism 19,[24][25][26][27] as well as poor oral hygiene, chronic oral trauma, previously existing local infection and a history of dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Historically, the risk of developing osteonecrosis (at any site) is four times higher in cancer patients than in the normal population and has multiple risk factors, including previous/ concomitant chemotherapy, regular steroid therapy, immunosuppressant therapy, radiation therapy, diabetes, hypertension, obesity, certain gene mutations, tobacco habit, alcoholism 19,[24][25][26][27] as well as poor oral hygiene, chronic oral trauma, previously existing local infection and a history of dental procedures. [25][26][27]31,32 Zoledronic acid is known to be more potent than all the other bisphosphonates and it is reported that patients taking zoledronic acid are 30 times more likely to develop osteonecrosis. 25 The patient had not used cigarette and alcohol.…”
Section: Discussionmentioning
confidence: 99%